ZnS thin films deposition by thermal evaporation for photovoltaic applications. (October 2015) - Benyahia, K.; Benhaya, A.; Aida, M. S.
Abstract: ZnS thin films were deposited on glass substrates by thermal evaporation from millimetric crystals of ZnS. The structural, compositional and optical properties of the films are studied by X-ray diffraction, SEM microscopy, and UV–VIS spectroscopy. The obtained results show that the films are pin hole free and have a cubic zinc blend structure with (111) preferential orientation. The estimated optical band gap is 3.5 eV and the refractive index in the visible wavelength ranges from 2.5 to 1.8. The good cubic structure obtained for thin layers enabled us to conclude that the prepared ZnS films may have application as buffer layer in replacement of the harmful CdS in CIGS thin film solar cells or as an antireflection coating in silicon-based solar cells.